Sustainable Writing Support: A Campus-wide Module to Support Bachelor Thesis Writing at a University of Technology - Andreas Eriksson; Carl Johan Carlsson; Fia Börjeson (Educare)
Higher education is today characterised by increasing student groups and high pressure on teaching staff. In these circumstances, it may be difficult to provide appropriate scaffolding of activities that many students find challenging, for example, academic and discipline-specific writing. It may also be difficult to align such support with principles associated with effective learning. In this paper, we present the design of the bachelor thesis writing support for students at a university of technology. The support is delivered by a communication division and reaches approximately 900 students each year. The paper describes the principles guiding the design and use results from a student survey to illuminate the challenges and affordances of the approach. The survey results show that students appreciate the module and its focus on dialogic feedback, student engagement and student activity. Our results also show that one of the challenges for some students is to negotiate advice from multiple sources, primarily content supervisors and writing staff. Despite such challenges, the design is an example of a sustainable, large-scale writing module based on research on feedback and learning.